2017
DOI: 10.1016/j.ccell.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Notch1 Activity Facilitates Metastasis

Abstract: Endothelial cells (ECs) provide angiocrine factors orchestrating tumor progression. Here, we show that activated Notch1 receptors (N1ICD) are frequently observed in ECs of human carcinomas and melanoma, and in ECs of the pre-metastatic niche in mice. EC N1ICD expression in melanoma correlated with shorter progression-free survival. Sustained N1ICD activity induced EC senescence, expression of chemokines and the adhesion molecule VCAM1. This promoted neutrophil infiltration, tumor cell (TC) adhesion to the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
217
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 260 publications
(240 citation statements)
references
References 69 publications
11
217
1
1
Order By: Relevance
“…Another potential application of GSi treatment based on our study is related to the capacity to inhibit metastasis, thus defining GSi as a “migrastatic” drug. Increasing evidence supports a role for NOTCH signaling in metastasis, exemplified by the capacity of NOTCH1 to trigger premetastatic niche formation . In CCA, we observed elevated NOTCH1 to be associated with lymph node metastasis in patients with advanced disease as well as enrichment of metastasis signatures in predicted GSi responders.…”
Section: Discussionsupporting
confidence: 60%
“…Another potential application of GSi treatment based on our study is related to the capacity to inhibit metastasis, thus defining GSi as a “migrastatic” drug. Increasing evidence supports a role for NOTCH signaling in metastasis, exemplified by the capacity of NOTCH1 to trigger premetastatic niche formation . In CCA, we observed elevated NOTCH1 to be associated with lymph node metastasis in patients with advanced disease as well as enrichment of metastasis signatures in predicted GSi responders.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, other groups have also demonstrated that the Notch signals in EC are involved in tumor progression and stem cell phenotype . Notch activation in EC promotes tumor cell migration and metastasis along with neutrophil infiltration …”
Section: Role Of Tumor Endothelial Cells In Tumor Progression and Metmentioning
confidence: 98%
“…Tumors hypoxia usually leads to massive cell necrosis and is not usually associated with tumor invasion or metastasis. Instead, additional microenvironmental cues, such as inflammatory cytokines and growth factors derived from immune cells, mesenchymal cells, senescence, or necrotic cells are required for EMT and subsequent tumor invasion and metastasis . It is unclear how cellular hypoxic responses and microenvironmental cues interact with each other in EMT induction resulting in tumor invasion and metastasis.…”
mentioning
confidence: 99%